2007
DOI: 10.2478/s11756-007-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcium oxalate crystals of some Crataegus (Rosaceae) species growing in Aegean region

Abstract: In this study, Ca oxalate crystals were isolated from the leaves and X-ray diffraction identified them as weddelite in Crataegus pontica C. Koch, C. stevenii Polar., C. monogyna ssp. monogyna Jacq. in C. orientalis var. orientalis Pallas ex Bieb. both whewellite and weddelite crystals were found. Although there were some differences among the soluble and insoluble oxalate contents, they were not notable in the species of C. stevenii (10%; 18%), C. orientalis (12.4%; 15%), C. monogyna (12.9%; 13%), whereas in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…In Rosaceae family, crystals have been observed only in the leaf of Crataegus (Demiray 2007) and Prunus virginiana (Lersten and Horner 2004). In this study, crystals were observed in the ovary wall of F. x ananassa.…”
Section: Discussionsupporting
confidence: 44%
“…In Rosaceae family, crystals have been observed only in the leaf of Crataegus (Demiray 2007) and Prunus virginiana (Lersten and Horner 2004). In this study, crystals were observed in the ovary wall of F. x ananassa.…”
Section: Discussionsupporting
confidence: 44%
“…The crystal occurs in different plant tissues, including leaves, stems, roots, seeds and flora of over 215 plant families (Franceschi and Horner, 1980;Lersten and Horner, 2000;Monje and Baran, 2002;Franceschi and Nakata, 2005;Korth et al, 2006;Demiray, 2007). The crystals are formed in calcium oxalate crystal idioblasts.…”
Section: Morphological Changes and Function Of Calcium Oxalate Crystamentioning
confidence: 99%
“…& Kit. ex Willd., while both tetragonal and prismatic crystals were reported for C. orientalis [34]. Furthermore, calcium oxalate crystals were also found in different parts of the leaf lamina in the genus Rosa L. [35] and Rosaceae family [25,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%